Trade and the pattern of European imperialism, 1492-2000 - Bonfatti, R (University of Oxford, 2012)
I construct a trade model of empire, and use it to interpret some of the key patterns in the history of European imperialism. I begin from the observation that trade was a key source of wealth for the colonies, and trade restrictions a key tool of extraction for colonial powers. But the value of this tool must be seen in relation to the value of colonial trade, and to the extent of international competition for it. The model interprets the colonial empires that emerged in the 16th-18th century as a set of political institutions designed to appropriate the value of colonial trade to the mother country, at a time in which colonial trade was both valuable and highly competed for. It explains the fluctuations in the fortunes of empire in the 19th and early 20th century with the rise of a clear industrial leader, Britain, and her subsequent decline. Finally, it attributes the fall of colonial empires to a secular fall in the importance of colonial trade, relative to trade between the industrial countries. I provide detailed historical evidence in support of these predictions. The model also has predictions for the impact of empire-building on trade relations between the imperial powers. These are consistent with the apparent inverse relation between European imperial expansion and globalization.